Визначення потенціалу енергозбереження процесу концентрації гідролізної сірчаної кислоти - Ульєв, Леонід Михайлович; Нехаенко, М. В.; Данілов, Юрій Борисович (НТУ "ХПІ", 2012)
The article is devoted to the studying of sulfuric acid concentration process. The main goal is determination of the energy saving potential for given process by using pinch-diagnostic. Data extraction, construction of the composite curves, determination of the energy targets and optimal temperature difference are discussed. A new heat-exchanger network is presented. It is concluded that modern project is cost effective
Keywords: пінч-аналіз; енергозберігаючі методи; суспензія сульфатів; охолоджуючий темплообмінник